Pengembangan Pendidikan Islam dalam Perspektif Filsafat Pendidikan Islam - Nurul Faizatus Sholikah; Faridi Faridi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The development of Islamic education from the perspective of Islamic educational philosophy includes a deep understanding of the goals, methods, foundations and curriculum that underlie Islamic education. Islamic educational philosophy provides a strong philosophical foundation in designing and implementing curriculum and teaching methods that are in accordance with Islamic values. This research uses a qualitative approach. Based on research results, Development of Islamic Education in the Perspective of Educational Philosophy. By applying the principles of Islamic educational philosophy, it is hoped that Islamic education can produce individuals who have a balance between knowledge and faith, and are able to carry out their role as servants of Allah and caliphs on earth.